2009
DOI: 10.1002/jcp.21906
|View full text |Cite
|
Sign up to set email alerts
|

Both B1R and B2R act as intermediate signaling molecules in high glucose‐induced stimulation of glutamate uptake in ARPE cells

Abstract: Bradykinin (BK) is a potent modulator of biological processes in the retina, and retinal pigment epithelial cells (RPE) and the regulation of glutamate are believed to be important in the pathogenesis of diabetic retinopathy. However, the mechanism by which BK regulates glutamate uptake in RPE cells in diabetic retinopathy is unknown. Here, we examined the involvement of BK receptors in high glucose-induced dysfunction of glutamate uptake in human ARPE cells. High glucose stimulated glutamate uptake and the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 47 publications
2
9
0
Order By: Relevance
“…It remains to be elucidated if phosphorylation of I-κB is not correlated with the reduction of total I-κB protein levels. In a previous report, we showed that the activation of NF-κB acts as an important mediator in BK action under diabetic conditions in human retinal pigment epithelial cells (Lim et al, 2009). We provide here further evidence that the BK-induced activation of NF-κB and I-κB in podocytes may be linked to high glucose-induced apoptosis in diabetic nephropathy.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…It remains to be elucidated if phosphorylation of I-κB is not correlated with the reduction of total I-κB protein levels. In a previous report, we showed that the activation of NF-κB acts as an important mediator in BK action under diabetic conditions in human retinal pigment epithelial cells (Lim et al, 2009). We provide here further evidence that the BK-induced activation of NF-κB and I-κB in podocytes may be linked to high glucose-induced apoptosis in diabetic nephropathy.…”
Section: Discussionsupporting
confidence: 57%
“…Endocannabinoids produce behavioral effects primarily by activating two specific receptors, cannabinoid receptor 1 (CB 1 R) and cannabinoid receptor 2 (CB 2 R). Previously, we demonstrated that KKS activation was involved in the high glucose-induced dysfunction of retinal pigment epithelial cells (Lim et al, 2009). We also demonstrated that CB 1 R activation is involved in high glucose-induced apoptosis in kidney mesangial cells (Lim et al, 2011).…”
Section: Introductionmentioning
confidence: 91%
“…Overall data support the important role played by BK and kinin receptors in regulating retinal vascular function in both control and diabetic conditions. The present work along with previous studies [15,19,20] also support a role of BK at the outer BRB although further experiments are necessary to evaluate BK-induced RPE dysfunction in vivo.…”
Section: Discussionsupporting
confidence: 80%
“…BK acts as a mediator of a wide variety of physiological and pathophysiological responses including vasodilation, increased vascular permeability and inflammatory cell recruitment, leading to tissue edema, perpetuation of inflammation and pain. The KKS including mRNAs for kinin B 1 and B 2 receptors is endogenously expressed in human ocular tissues, and a complete system is expressed in human retina and in human RPE [14,15]. In addition, increased levels of components of the KKS have been detected in the vitreous of patients with diabetic retinopathy and in a rat model of carbonic anhydrase-I-induced retinopathy [16] and a role of the KKS in the development of diabetes-induced vascular dysfunction in the retina has been contemplated [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…BK has been shown to mediate a variety of activities within neuronal tissues, including stimulating the glutamate release from astrocytes and modulating activities of sensory ion channels (Parpura et al, 1994; Mizumura et al, 2009; Liu et al, 2010a). In addition, both B1R and B2R activation can regulate glutamate clearance by retinal pigmented epithelial cells through a PKC-Akt-COX-2 signaling cascade (Lim et al, 2009). The potential effects of intraocular activation of the KKS on the neuroretina are largely unknown.…”
Section: Introductionmentioning
confidence: 99%